Association between Flat Foot Severity and Low Back Pain Recurrence among Pre-Clinical Medical Students: A Cross-Sectional Study - Annisa Ummi Hafizhah Arif Fiyanto; Vonny Fibrianty Goenawan (Lumina : Indonesian Journal of Neurology, 2025)
Background: Low back pain (LBP) affects over 619 million people globally and is highly prevalent among medical students. Flat foot (pes planus), a biomechanical alteration involving the collapse of the medial longitudinal arch, may contribute to spinal stress and LBP recurrence, yet remains underexplored in young adult populations. Methods: This cross-sectional study involved 67 pre-clinical medical students aged 19–23 years with a history of recurrent LBP in the past year. LBP frequency was assessed using the Nordic Musculoskeletal Questionnaire and Numeric Rating Scale (NRS). Foot arch structure was evaluated via Clarke’s Angle, classifying flat foot severity into mild (35°–41°), moderate (30°– 34.9°), and severe (<30°). Data were analysed using Chi-square tests, with significance set at p < 0.05. Results: LBP was reported by 80.6% of participants, with flat foot classified as mild in 43.3%, moderate in 37.3%, and severe in 19.4%. A significant association was found between flat foot severity and LBP recurrence (p < 0.001). Students with mild or moderate flat foot had a lower odd of experiencing moderate-frequency LBP compared to those with severe flat foot (OR = 0.152 95% CI: 0.048–0.483). Discussion: These findings support the notion that structural abnormalities of the foot, particularly flat foot, may contribute to the recurrence and persistence of LBP by influencing spinal posture, altering mechanical load distribution, and affecting neuromuscular stability. Conclusion: Flat foot severity is significantly associated with the recurrence of LBP in medical students. Early identification and foot posture assessment may help inform preventive and corrective interventions for recurrent LBP.